2009
DOI: 10.1002/cphc.200900289
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Storage Mediated by Pd and Pt Nanoparticles

Abstract: The hydrogen storage properties of metal nanoparticles change with particle size. For example, in a palladium-hydrogen system, the hydrogen solubility and equilibrium pressure for the formation of palladium hydride decrease with a decrease in the particle size, whereas hydrogen solubility in nanoparticles of platinum, in which hydrogen cannot be stored in the bulk state, increases. Systematic studies of hydrogen storage in Pd and Pt nanoparticles have clarified the origins of these nanosize effects. We found a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
147
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(151 citation statements)
references
References 123 publications
4
147
0
Order By: Relevance
“…Bulk and nanoparticle metal hydrides have been extensively studied due to their importance in many applications such as hydrogen storage [16,17,18,19,20,21]. The novel scheme [8] is based on the modification of the optical properties of nanoparticles, i.e., the shift in energy of the LSP peak, during the H absorption process.…”
Section: Introductionmentioning
confidence: 99%
“…Bulk and nanoparticle metal hydrides have been extensively studied due to their importance in many applications such as hydrogen storage [16,17,18,19,20,21]. The novel scheme [8] is based on the modification of the optical properties of nanoparticles, i.e., the shift in energy of the LSP peak, during the H absorption process.…”
Section: Introductionmentioning
confidence: 99%
“…In general, pure Au, Pd, and Cu themselves are little effective toward MOR in acidic electrolyte. As mentioned above, because of highly miscible of the Pd and Pt atoms, the pseudo Pt–Pd alloy structure should be formed at the internal surface of mesoporous PdPt spheres, which is favorable for reducing the electronic binding energy in Pt and improving catalytic activity 23. Also, it is clear that the introduction of the third element (Au or Cu) indeed plays an important role for further enhancing the electrocatalytic activity toward MOR because a moderate decrease of CO adsorption is caused by incorporating Au or Cu into the catalysts.…”
mentioning
confidence: 99%
“…6,12) Also, Pt nanoparticles showed a monotonic relationship between the H 2 pressure and the concentration. 6,7) The hydrogenation during pressurization and the dehydrogenation during depressurization are common to conventional hydrogen-storage materials and advanced nanoparticles, irrespective of the presence or absence of plateau region. However, the nanoporous Pt exhibited the dehydrogenation during pressurization and the hydrogenation during depressurization at high H 2 pressure.…”
Section: Methodsmentioning
confidence: 95%
“…5) Recently, it has been reported that Pt nanoparticles with a diameter of 2-3 nm absorb hydrogen, whereas bulk Pt does not. 6,7) In this Rapid Publication, we describe the abnormal hydrogen absorption/desorption properties of nanoporous Pt, which is produced by dealloying, with a ligament size of $3 nm. High H 2 pressure (> 1 MPa) leads to dehydrogenation, which is opposite to the hydrogenation behavior in hydrogen-absorbing materials including advanced nanoparticles.…”
Section: Introductionmentioning
confidence: 99%